PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERASI - BADARUDIN, AFIS; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2018)
This study aims to examine the influence between the application of corporate social responsibility and intellectual capital to the value of the company that listed in LQ45 on Indonesian Stock Exchange (IDX) year 2013-2016, in addition this study also test the financial performance as a moderation variable. The method used in this study is quantitative with the techniques of collecting documentation, namely through annual reports and financial statements of the company. This research use Structural Equation Modeling (SEM) analysis.The result of Structural Equation Modeling (SEM) analysis using WarpPLS 5.0 shows that corporate social responsibility has an effect on company value, intellectual capital has an effect on company value, financial performance can not moderate the relationship between corporate social responsibility to company value, and financial performance can moderate by weakening the relationship between intellectualcapital to company value.